Food Security and Conflict - Bora, Saswati; Ceccacci, Iride; Delgado, Christopher; Townsend, Robert (World Bank, Washington, DC, 2012)
Finds that food insecurity has clearly contributed to outbreaks of social unrest or worse, while conflict has induced situations of food insecurity. The factors of population growth, competitive pressure on land and water use, climate change, and price volatility tend to increase stress, raising the risk of civil unrest or conflict. The most fragile countries often have the least capability to respond, falling victim to the vicious circle of conflict and food insecurity. Food aid, including insurance options for agricultural commodities, limits immediate food insecurity impacts of conflict and continues to alleviate even greater harm to innocent people. Such aid can also assist in better transition to longer-term agricultural productivity growth and local market development, especially in rural areas that tend to be poorer; however, it is not possible to significantly reduce conflict on a sustained basis without significant new investment and partnerships in key areas of agriculture and rural development.